Mineralogy for Petrologists. Optics, chemistry and occurrence of rock-forming minerals - Demange M. Michel (London, Taylor & Francis, 2012)
Comprising a guidebook and a full color CD-ROM, this reference set offers illustrated essentials to study mineralogy, applied to petrology. While there are some excellent reference works available on this subject, this work is unique for its data richness and its visual character. With a collection of images that excels both in detail and aesthetics, 151 minerals are presented in more than 400 plates. Different facies and paragenesis, both in natural polarized light, are shown for every mineral and optical data, sketches of the crystal habitus, chemical composition, occurrence and a brief description are included. The accompanying user guide gives a general introduction to microscope mineral observation, systematic mineralogy, mineral chemistry, occurrence, stability, paragenesis, structural formula calculation and its use in petrology. This compact set will serve as a field manual to students, researchers and professionals in geology, geological, mining, and mineral resources engineering to observe and determine minerals in their studies or field work.